Whole exome sequencing identifies a homozygous nonsense variation in ALMS1 gene in a patient with syndromic obesity. Issue 2 (March 2017) - Das Bhowmik, Aneek; Gupta, Neerja; Dalal, Ashwin; Kabra, Madhulika
Summary: In the present study we report on genetic analysis in a patient with developmental delay, truncal obesity and vision problem, to find the causative mutation. Whole exome sequencing was performed on genomic DNA extracted from whole blood of the patient which revealed a homozygous nonsense variant (c.2816T > A) in exon 8 of ALMS1 gene that results in a stop codon and premature truncation at codon 939 (p.L939Ter) of the protein. The mutation was confirmed by Sanger sequencing. Exome sequencing was helpful in establishing diagnosis of Alstrom syndrome in this patient. This case highlights the utility of exome sequencing in clinical practice.